Blooming fitoplankton di perairan Kepulauan Seribu - Mursalin Mursalin; Reza Zulmi; Marfian Dwidima Putra; Luluk Dwi Wulan Handayani; Irza Arnita Nur (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
The phenomenon of phytoplankton blooms often occurs in the waters of the Thousand Islands (Jakarta Bay). On October 15, 2020, the blooming occurred again. Therefore, this study was conducted to determine the types of phytoplankton that were blooming in Jakarta Bay. Real time sampling of the blooming phytoplankton was carried out. Furthermore, the samples were directly analysed at the Laboratory of Productivity and Aquatic Environment, IPB University. The parameters analysed were the composition of phytoplankton species and water quality. Phytoplankton underwent blooming was Trichodesmium. Blooming frequently occurred in the waters of the Thousand Islands. This is closely related to seasonal changes and increased nutrient content in the waters, especially nitrate and orthophosphate, which support the rapid growth of phytoplankton (blooming).